1993
DOI: 10.1002/1097-0142(19930101)71:1<124::aid-cncr2820710120>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Specific skin manifestations in acute leukemia with monocytic differentiation a morphologic and immunohistochemical study of 11 cases

Abstract: Background. Monocytic differentiation is present in the myelomonocytic (M4) and monocytic (M5) type of acute myeloblastic leukemia. Infiltration of the skin in acute myelomonocytic leukemia occurs in 10–20% of patients, the skin lesions occasionally being the first symptom, even preceding monocytosis. Methods. Eleven patients with myelomonocytic (n = 2) and monocytic leukemia (n = 9) were studied who had skin manifestations. Results and Conclusions. Clinically, all patients showed disseminated papules or nodul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1
6

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 14 publications
3
35
1
6
Order By: Relevance
“…The reason for this is uncertain, but may involve timing of the biopsy (longer-standing lesions would presumably have a larger number of malignant cells), preferential biopsy of the center vs. the leading edge of a lesion, or some other factor. Moreover, the clinical significance of differentiating the de novo vs. secondary cases (which could, of course, have been resolved on clinical grounds) is likely of little consequence in our patients, since survival for patients in our series was almost uniformly poor; patients do not appear to have benefitted from recent innovations in chemotherapeutic regimens or bone marrow transplant, as previous studies performed over a decade ago have demonstrated similar findings (8,11).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…The reason for this is uncertain, but may involve timing of the biopsy (longer-standing lesions would presumably have a larger number of malignant cells), preferential biopsy of the center vs. the leading edge of a lesion, or some other factor. Moreover, the clinical significance of differentiating the de novo vs. secondary cases (which could, of course, have been resolved on clinical grounds) is likely of little consequence in our patients, since survival for patients in our series was almost uniformly poor; patients do not appear to have benefitted from recent innovations in chemotherapeutic regimens or bone marrow transplant, as previous studies performed over a decade ago have demonstrated similar findings (8,11).…”
Section: Discussionsupporting
confidence: 66%
“…Our data show that the distribution of lesions favors the upper body. In all series in which an appropriate level of detail was provided (7)(8)(9)(10)(11)(12)(13)(14), the most common bone marrow diagnosis was AML, and cases with myelomonocytic or monoblastic/monocytic differentiation were prominently represented. When reported, CMS was noted to follow the initial bone marrow diagnosis (6,12,13), though most patients eventually have bone marrow involvement.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Jedoch bei nur 2 ± 8 % der AML-Patienten treten Hautinfiltrate mit bioptisch nachweisbaren Tumorzellen auf [2,3]. In der Untergruppe der monozytären und myelomonozytären Formen sind hingegen bis zu 30 % der Erkrankten betroffen [4,5]. …”
Section: Kommentarunclassified